RISK FACTORS FOR CHRONICLE DEGENERATIVE DISEASES IN OFFICIALS OF UNIVERSITY (Fiep Bulletin - online, 2013)
The job has been extended to the private life of workers who has a limited time to use in the prevention and health maintenance. Based on that, the objective of the study is to identify among the employees of a private education institution which are the risk factors for the health. We evaluated 48 subjects, 33 females and 15 males, officials of Don Bosco School. A questionnaire was used to check the living habits of officials about the risk factors, measurement of heart rate (HR) and systolic blood pressure (SBP) and diastolic (DBP), measurements of body mass (CM) and height (ES) , Girth waist and hip and a protocol with 3 skinfolds. For the treatment of data was used a descriptive analysis, mean, standard deviation, minimum and maximum values of the variables. The average age was 32.17 ± 10.69 years for women and 41.26 ± 14.03 years for men. The population in mostly did not practice physical activities, 70% of women and 60% of men. Of all the officials only 3, (6%) of women are smokers. As for the consumption of alcohol, the consumption among men was higher, 57% vs. 15% in women. In the female population, 82% male and 73% have a family history with risk diseases, like hypertension, diabetes, obesity and heart disease. Women had SBP of 126 ± 16mmHg and men had 142 ± 19mmHg and DBP of 77 ± 6mmHg ± 18mmHg and 87, respectively. The average heart rate for women was 77 ± 8bpm and for men 74 ± 12bpm. The average BMI among women was 25.51 ± 4.64 kg / meters and for men were 27.30 ± 3.79 kg / m². The value found for ICQ women was 0.79 ± 0.06 and 0.91 ± 0.06 for men. The average percentage of fat in women employees was 29.9 ± 4.17 and 21.11 ± 3.66 for men. With this stud we can verify that officials of the institution have risk factors for health such as blood pressure changed, hips waist index, body mass index and fat percentage below the ideal. The family history of disease related with risk factors also proved to be a negative factor. Only smoking can be considered positive factor, because the minority said to be a smoker.
Keywords: Body Composition; Body mass index; risk factors